Storming the Gates. - Newman, Nathan (American Prospect)
The U.S. Department of Justice is engaged in an antitrust case against Microsoft, but a bigger threat to the company could come from open-source software. Unlike the commercial software of company's like Microsoft, open-source software is intended to be studied and improved upon by other programmers. This type of software emerged as a reaction to the proprietary standard set by Microsoft. Many growing computer companies saw open-source software as the only way to survive in the face of the onslaught from Microsoft. The government should not restrict innovation at Microsoft by being overly punitive, but it should promote open-source software as a positive policy option.